INFLUENCE POWER PULL AND FACILITY AGAINST INTEREST VISITING TRAVELER TO OBJECTS TOUR WATER JUMP EMBUN WATERFALL, KEPAHIANG REGENCY - Ratnawili; Sendra Hadiatna (Universitas Muhammadiyah Bengkulu, 2025)
The purpose of this research is to determine the influence of attractions and facilities on the interest of tourists to visit the Curug Embun Waterfall tourist attraction in Kepahiang Regency. The population in the study were all visitors to the Curug Embun Waterfall tourist attraction in Kepahiang Regency. The technique for determining the sample was purposive sampling with the number The sample was 90 respondents. Data collection using questionnaire And analysis data use model regression linear multiple coefficient , coefficient of determination and hypothesis testing. The results of the study show that attractiveness has an effect positive on Tourist Visiting Interest, Facilities have a positive effect on Tourist Visiting Interest, Attractions and facilities together contribute to the influence on Tourist Visiting Interest, amounting to 80.3% while the remaining 19.7% is influenced by other variables that are not included in this research model. The results of the hypothesis test in this study indicate that there is a significant influence between attractions and facilities on tourist visiting interest at the Curuk Embun waterfall tourist attraction